Age at Menarche in Women With Bipolar Disorder: Correlation With Clinical Features and Peripartum Episodes - Rosso, Gianluca; Aragno, Elena; Mehanović, Emina; Di Salvo, Gabriele; Maina, Giuseppe (Frontiers in Psychiatry, 2020)
Background Bipolar disorder (BD) is related to reproductive cycles. However, findings on putative correlation between age at menarche and course of BD are particularly scarce and conflicting. The aim of the present study is to analyze the relationship between age at menarche and characteristics of BD, including comorbid medical conditions and peripartum mood episodes. Methods The study sample consists of 288 women with BD type I, II, or not otherwise specified (NOS). Age at menarche was both considered as a continuous variable and categorized into three groups: early menarche (≤11 years), normal menarche (12–14 years), and late menarche (≥15 years). The study focused on two sets of comparisons, by age at menarche and women with vs. without children. Spearman correlation matrix was produced to calculate correlations between the variables of interest. Socio-demographic and clinical characteristics between early, normal and late menarche, and women with vs. without children were examined through descriptive statistics. Finally, adjusted logistic regression analysis was run to examine the association between variables. Results Out of 288 women included in the study, 21.5% had early menarche, 55.6% had normal, and 22.9% had late menarche. Women with early menarche had higher rates of metabolic syndrome compared to women with normal menarche even after adjustment for age. The subgroup of women with children does not present clinical differences compared to women without children except a lower rate of psychiatric comorbidities. At least one mood episode with peripartum onset occurred in 29.6% of the women with children. After controlling for confounding variables, women with late menarche were associated with lower probability of BD peripartum episodes compared to women with normal menarche. Conclusion Age at menarche may be related to specific characteristics of women with BD. The results deserve to be deepened in further studies.